Cultivating the heart : feeling and emotion in twelfth- and thirteenth-century religious texts - Lazikani, Ayoush Sarmada, 1987- (Cardiff : University of Wales Press, 2015)
Cultivating the Heart reveals the languages of feeling in a range of religious texts from the High Middle Ages.
Front Cover; Series Editors' Preface; List of Illustrations; Acknowledgements; List of Abbreviations; Note on Editions and Translations; Introduction: Feeling in the High Middle Ages; 1 Upon a Spiritual Cross: Feeling in the Lambeth and Trinity Homilies; 2 The Gnawed Hand: Presence and Absence of Feeling in the Early South English Legendaries; 3 Co-feeling: Compassion in Ancrene Wisse and the Wooing Group; 4 Call Me Bitter: Feeling and Sensing in Passion Lyrics; Conclusion; Notes; Select Bibliography; Index; Back Cover.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Religious literature -- 12th century; Religious literature -- 13th century; Emotions -- Religious aspects -- Christianity; Emotions in literature; Christian literature, English -- History and criticism; English literature -- Middle English, 1100-1500 -- History and criticism; Littérature chrétienne anglaise -- Histoire et critique; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Émotions -- Aspect religieux -- Christianisme; Littérature religieuse -- 12e siècle.; Littérature religieuse -- 13e siècle.; RELIGION -- Christian Theology -- Systematic; RELIGION -- Christianity -- General; Emotions in literature; Emotions -- Religious aspects -- Christianity; Religious literature; 1100-1299; Electronic books; Criticism, interpretation, etc